Toxicological Effects of Cadmium on Mammalian Testis - Zhu, Qiqi; Li, Xiaoheng; Ge, Ren-Shan (Frontiers in Genetics, 2020)
Cadmium is a heavy metal and humans expose it possibly via contaminated foods and smoking. In humans and other mammals, cadmium causes damage to male testis. In this review, we summarize the effects of cadmium on development and function of the testis. Cadmium causes severe structural damage of the seminiferous tubules, Sertoli cells, and blood-testis barrier, thus leading to the loss of sperm. Cadmium hinders Leydig cell development, inhibits Leydig cell function, and induces Leydig cell tumors. Cadmium also disrupts the vascular system of the testis. Cadmium is a reactive oxygen species inducer and possibly induces DNA damage, thus epigenetically regulating somatic cell and germ cell function, leading to male subfertility/infertility.